'For My Own Good. All Causes shall Give Way' (Macbeth): Superego Workings in Narcissistic States of Mind and Character. (5th December 2021) - Harding, Celia
Abstract : In this paper, I argue that moral function in narcissistic states of mind is founded in a self‐preservative ethic aiming to control, rather than regulate, relations between self, others and realities. I propose a working model of superego functioning comprising ego ideal, social rules, ego capacities devoted to moral duties and repressed aggressive impulses recycled through superego activities. In narcissistic states the ego is fragile due to developmental deficits. Ego weakness is compensated by identification with an omnipotent ideal ego and resort to weaponized moral accusations – directed at self and/or objects – to fend off realities which threaten to disturb precarious narcissistic equilibrium. I will illustrate with case material how my fears of facing my failures to live up to my own analytic ideal ego expectations colluded with my patient's fears of facing the reality of her own limitations and needs. I needed to develop my understanding of my own superego processes before I could enable my patient to modify her omnipotent expectations of herself and relinquish her efforts to 'force' herself to control everything by punishing herself mercilessly when she failed.